Tecnic of Cervical Esophageal Anastomosis - Allende, Daniel A; Miranda, Eduardo; Pizarro, Pedro (Cirugía del Uruguay, 1980)
A tecnical variation of cervical esophagus - gastrostomy is exposed. It's principal caracteristics are: surgical field widence, by ECM and prethyroid muscies section; delicate management of visceral end, trowel widence anasto·mosis and prethyroid muscles suture to replacement organ, in arder to diminish the traction.